50. Peripheral neuropathy associated with Duodopa infusion: neurophysiological retrospective study. Issue 12 (December 2016) - Simioni, V.; Sette, E.; Capone, J.G.; Preda, F.; Granieri, E.; Sensi, M.; Tugnoli, V.
Abstract : Subacute and chronic peripheral neuropathies (PN) have been reported in Parkinson's disease (PD) patients treated with levodopa/carbidopa intestinal gel infusion (Duodopa), but only one study evaluated a long term follow up. We performed a retrospective electrophysiological study of 23 PD patients treated with Duodopa with a follow up period of 18 months. The electrophysiological assessments of 23 patients have been retrospectically collected and evaluated at baseline (before Duodopa infusion) and at 6, 12 and 18 months. Nerve conduction studies were obtained for the bilateral median, ulnar, tibial and peroneal motor nerves and for the bilateral median, ulnar and sural sensory nerves. During a follow-up period of 18 months, a statistically significant decrease in mean sural SAP amplitude was recorded. At baseline 5/23 patients showed PN. During the follow up, one patient developed a subacute PN and two patients developed a sensory-motor PN. Duodopa infusion was immediately halted in the subacute case, while the infusion therapy was not interrupted in chronic forms. All patients were supplemented with vitamin B12 and folate. Serial electrophysiological evaluations are mandatory in patients treated with Duodopa, given the possible risk of PN.